Basic Principles for Calculating Heat Exchanger Characteristics under Conditions of Environmental Heat Losses - B. A. Bayrashevsky; N. P. Boroushko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers two most characteristic models of heat exchange mechanisms in heaters with due account of environmental heat losses. As a result of executed investigations a list of corresponding engineering formulae has been developed which can be used for determination of heat engineering characteristics of heat exchangers and calculation of heating modes of their operation.Authors of the paper have elaborated a special «Heat Exchanger» programming file that corroborates reliability of the executed analysis and makes it possible to carry out a number of the required calculations.